Synergistic Effects of Exercise Training and Vitamin D Supplementation on Mitochondrial Function of Cardiac Tissue, Antioxidant Capacity, and Tumor Growth in Breast Cancer in Bearing-4T1 Mice - Jafari, Ali; Sheikholeslami-Vatani, Dariush; Khosrobakhsh, Farnoosh; Khaledi, Neda (Frontiers in Physiology, 2021)
Both regular exercise training and vitamin D consumption are beneficial for patients with cancer. The study investigated the effects of interval exercise training (IET) or/and vitamin D supplementation on the gene expression involved in mitochondrial function of heart tissue, tumor size, and total antioxidant capacity (TAC) in breast cancer model mice. We assigned random Forty female NMRI mice to five equal groups (n=8); the healthy control group (H.C), cancer control group (Ca.C), cancer with the vitamin D group (Ca.VD), cancer exercise group (Ca.Ex), and cancer exercise along with the vitamin D group (Ca.Ex.VD). Forty eight hours after treatment, we anesthetized the animals and performed the isolation of heart tissue and blood serum for further studies. The results showed that the lowest mean body weight at the end of the treatments was related to Ca.C (p=0.001). Vitamin D treatment alone has increased tumor volume growth by approximately 23%; in contrast, co-treatment with exercise and vitamin D inhibited tumor growth in mice (P=0.001), compared with the cancer control (12%).TAC levels were higher in the group that received both vitamin D and exercise training (Ca.Ex.VD) than in the other treatment groups (Ca.VD and Ca.Ex) (p=0.001). In cardiac tissue, vitamin D treatment induces an elevation significantly of the mRNA expression of Pgc1-α, Mfn-1, and Drp-1 genes (p=0.001). The study has shown the overexpression of vitamin D in female mice, and synergistic effects of interval exercise training with vitamin D on weight loss controlling, antitumorigenesis, improvement of antioxidant defense, and the modulation of gene expression. The synergistic responses were likely by increasing mitochondrial fusion and total antioxidant capacity to control oxidative stress. We recommended being conducted further studies on mitochondrial dynamics and biogenesis focusing on risk factors of cardiovascular disease in patients with breast cancer.